Preclinical safety and burn wound healing activity of “Novostron”, a novel topical iodine-based therapeutic - Nailya Ibragimova; Arailym Aitynova; Seitzhan Turganbay; Marina Lyu; Alexandr Ilin; Tamari Gapurkhaeva; Galina Ponomareva; Karina Vassilyeva; Diana Issayeva; Amirkan Azembayev; Serzhan Mombekov; Aralbek Rsaliyev; et al. (PLoS ONE, 2025)
Iodine-based antiseptics are essential in wound care but are often limited by cytotoxicity, instability, and rapid iodine release. Novostron is a novel polymer–iodine complex incorporating dextrin, polyvinyl alcohol, and metal ions, designed to enable controlled iodine release. Structural integrity and composition were confirmed by ¹H and 13 C NMR spectroscopy and physicochemical analysis, indicating a molecular weight of ~9500 g/mol, a pH of 4.23, and an iodine content of 8.13%. Pharmacokinetic analysis in rabbits demonstrated that following a single dermal application, systemic iodine absorption was minimal, with peak blood iodine concentrations remaining within physiological limits and rapid elimination within 24 hours. Evaluation of thyroid function revealed no significant changes in serum T₃, T₄, or TSH levels compared with those of the controls, confirming that topical application of Novostron does not disrupt thyroid homeostasis. In compliance with OECD guidelines in rabbits, guinea pigs, and rats, Novostron showed no signs of dermal irritation, skin sensitization, or systemic toxicity (LD₅₀ > 2000 mg/kg). In a rat cotton pellet granuloma model, Novostron significantly reduced the inflammatory mass (23.65% inhibition), supporting its anti-inflammatory potential. In a murine burn model, Novostron accelerated wound contraction (25.95% at day 10), increased epidermal thickness, and enhanced collagen deposition (~44%), outperforming controls and matching or exceeding betadine. These findings suggest that Novostron promotes tissue repair by modulating inflammation. Overall, Novostron demonstrated a favourable preclinical safety and efficacy profile, and its polymer–iodine composition, which enables controlled release and localized activity highlights its potential as a promising topical therapeutic. However, the study was limited to animal models and short-term observation; further long-term and clinical investigations are needed to confirm its translational potential in human wound healing.